Artificial dissipation model applied to Euler equations for analysis of supersonic flow around a geometric configurations ramp and diffusor type - Jussiê Soares da Rocha; Edisson Sávio de Góes Maciel; Carlos Brayner de Oliveira Lira; Pedro Augusto Silva de Sousa; Raimundo Nonato Correia Neto (Brazilian Journal of Radiation Sciences, 2022)
Very High Temperature Gas Cooled Reactors - VHTGRs are studied by several research groups for the development of advanced reactors that can meet the world's growing energy demand. The analysis of the flow of helium coolant around the various geometries at the core of these reactors through computational fluid dynamics techniques is an essential tool in the development of conceptual designs of nuclear power plants that provide added security. This analysis suggests a close analogy with aeronautical cases widely studied using computational numerical techniques to solve systems of governing equations for the flow involved. The present work consists in using the DISSIPA2D_EULER code, to solve the Euler equations in a conservative form, in two-dimensional space employing a finite difference formulation for spatial discretization using the Euler method for explicit marching in time. The physical problem of supersonic flow of helium gas along a ramp and diffusor configurations is considered. For this, the Jameson and Mavriplis algorithm and the linear artificial dissipation model of Pulliam was implemented. A spatially variable time step is employed aiming to accelerate the convergence to the steady state solution. The main purpose of this work is obtain computational tools for flow analysis through the study the cited dissipation model and describe their characteristics in relation to the overall quality of the solution, as well as obtain preliminary results for the development of computational tools of dynamic analysis of helium gas flow in gas-cooled reactors.